Associated brain abnormalities in patients with corpus callosum anomalies - Tekgül, Hasan; Dizdarer, Gülşen; Yalman, Osman; Şener, Nuri; Yünten, Nilgün; Tütüncüoğlu, Sarenur (The Turkish Journal of Pediatrics, 1999)
Forty-nine patients with corpus callosum (CC) anomalies were evaluated in terms of the clinical features and magnetic resonance imaging (MRI) findings. CC anomalies were classified as CC agenesis: 6 (12%), CC hypogenesis: 5 (10%), and CC hypoplasia: 38 (78%). In the CC hypoplasia group the mean value of the genu thickness of the CC was 0.29 ± 0.1 cm, which was less than the normal value of the age-matched normal children (normal range: 0.6-1.2 cm). The associated brain abnormalities were in five distinct groups: gray matter abnormalities, white matter abnormalities, midline brain structure defects, cortical atrophy, and encephalomalacia. There was no uniformity for the clinical spectrum of CC anomalies. Microcephaly, developmental delay and seizures were the prominent findings in patients. The clinical features were more severe in cases with associated brain anomalies.
Keywords: corpus callosum; magnetic resonance imaging; brain abnormalities